Handbook of emotional disorders in later life - Laidlaw, Ken (Oxford University Press, 2008)
The editors bring together chapters by experienced trainers and clinicians that cover all the significant problems and issues in the assessment and treatment of emotional disorders in later life. The introductory chapters examine the individual, social, cultural and physical experience of ageing, and provide an essential background for a caring and professional understanding of related emotional disorders and their effective treatment. Throughout the book, key research and clinical experience is reported as underlying evidence based treatment, but the emphasis is on practical guidance for assessment and interventions, rather than detailed discussion of methodological issues. With each chapter written by a specialist in their field, a range of expertise is provided in a single source, making this book an invaluable resource for anyone dealing with the mental health needs of older people